A Newly Designed Analytical Line to Examine Fluid Inclusion Isotopic Compositions in a Variety of Carbonate Samples. (6th April 2018) - Dassié, Emilie P.; Genty, Dominique; Noret, Aurélie; Mangenot, Xavier; Massault, Marc; Lebas, Nicolas; Duhamel, Maxence; Bonifacie, Magali; Gasparrini, Marta; Minster, Benedicte; Michelot, Jean‐Luc
Abstract: δ 18 O and δD of fluid inclusions in carbonates provide insights into temperatures and fluid chemical compositions prevailing during the carbonate precipitation, however, various analytical restrictions limit a wider application of this proxy. This paper presents a new fluid inclusions isotopic analytical line coupled to an online cavity ring‐down spectrometer that increased the analytical productivity up to 10 carbonate samples per working day. This efficiency allowed for the first time to assess the reliability a large set of water samples with size ranging from 0.1 to 1 µL. Good reproducibility (±0.5‰ for δ 18 O and ± 2‰ δD; 1σ) is obtained for water quantity superior or equal to 0.3 μL and no evidence of memory effect is found. The line is further tested using two types of natural carbonates: (1) modern speleothems samples from caves for which δ 18 O and δD values of drip water were measured and (2) diagenetic carbonates for which the δ 18 O of the parent water were independently back‐calculated from carbonate clumped isotope Δ47 measurements. Speleothem fluid inclusion values despite falling close to the Global Meteoritic Water Line are not always representative of the isotopic composition of the parent drip water. Results on diagenetic cements show that the δ 18 Owater values measured in fluid inclusions agree, within 1%, with the δ 18 Owater independently derived from Δ47 measurements. Overall, this study confirms the reliability and accuracy of the developed analytical line for carbonate fluid inclusion analyses with a good reproducibility obtained for water quantity above 0.3 μL. Key Points: A new fluid inclusion analytical line with a productivity up to 10 carbonate isotopic measurements per working day A new reliable and accurate fluid inclusion analytical line for δ 18 O and δD fluid inclusion analyses in carbonates Fluid inclusion δ 18 O of diagenetic cements agree, within 1‰, with the δ 18 O independently derived from Δ47 measurements